Distress management in cancer patients：Guideline implementation based on CAN-IMPLEMENT - Liang Fu; Xiaoju Zhang; Yan Hu; Zhenqi Lu; Yang Yang; Mingzhu Huang; Yuanyuan Li; Fuzhong Zhu; Yang Wang; Zhe Huang (Elsevier, 2022)
Objective: To standardize the distress management of gastric cancer patients receiving chemotherapy, the adapted Cancer-related Distress Management Guidelines were implemented in nursing practice among gastric cancer patients receiving chemotherapy based on A Guideline Adaptation and Implementation Planning Resource (CAN-IMPLEMENT). Methods: Based on the theoretical framework of CAN-IMPLEMENT, A multidisciplinary team was established, barriers and facilitators obstacles of guidelines implementation in medical oncology units were assessed, corresponding solutions were formulated, the guidelines implementation process was monitored, and implementation results were evaluated. Results: The multidisciplinary team developed review criteria, standardized work paths, assessment tools, training manuals for healthcare professionals, education manuals for patients and their caregivers. After guidelines implementation, the completion rate of the distress management record came up to 97.9% (189/193). From September 2017 to December 2018, the compliance of medical staff on most items in the audit checklist was improved, ranging from 57.1% (100/175) to 100.0% (193/193). The positive distress rate of gastric cancer patients receiving chemotherapy was decreased from 22.7% (32/141) to 9.3% (18/193) (P < 0.05), and the Median (range) of the distress score declined from 2 (0-9) to 0 (0-7) (P < 0.001). Conclusions: The implementation of guidelines based on CAN-IMPLEMENT promotes the establishment of a distress management system in the medical oncology units. The review standards, standardized work paths, and evaluation tools for distress in cancer patients formulated by the multidisciplinary team had clinical applicability and effectiveness. Quality control in the practice of distress management was effective. The compliance of healthcare professionals with distress management was improved. The distress of gastric cancer patients receiving chemotherapy was alleviated effectively.